Development of AI-Assisted Animated Video Learning Media to Improve the Critical Thinking Skills of Grade IV Students in Elementary Schools - Sari, Maya; Sari, Mawar; Sri Anum, Dani; Afkar, Alysa Humairah; Niha, Sarah Atun; Nadia, Sherly; Rahayu, Sri; Sundari, Aisyah; Zahro, Naila maulani (Civiliza Publishing, Indonesia., 2025)
The advancement of digital technology today requires innovation in learning media, especially those that can help develop children's critical thinking skills at the elementary school level. Animated videos that utilize artificial intelligence or AI technology are one of the media alternatives that are quite promising. The purpose of this study is to create learning media in the form of AI-based animation videos that are indeed suitable for use in improving critical thinking skills in grade IV elementary school students. This research uses the R&D (Research and Development) method by conducting a literature review as the foundation. The data used came from journal articles both national and international in the last five years that discussed digital learning media, animated videos, AI technology, and critical thinking skills. From the results of the literature review conducted, it can be seen that animated video media can indeed improve students' critical thinking skills because the material is presented visually, contextually, and there are interactive elements. The use of AI in the creation of animated videos also makes the development process more efficient and the quality of the material presentation increases. From the results of this study, it can be concluded that AI-based animation video learning media has great potential to be applied in grade IV elementary school learning in order to support the development of students' critical thinking skills.